“Guerra ao terror”: uma guerra contra o terrorismo ou um pretexto para justificar políticas de conquista global? - Weber, Larissa (2018)
This study aims to analyze the implications of the terrorist attacks of September 11 in U.S. security policy and the establishment of a global counterterrorism regime at the expense of the international human rights, revealing a picture of regression. At first, we try to understand the central concepts used for the elaboration of this work: terrorism, war on terrorism and human rights. It is dedicated to the study of the figure of a very specific internal enemy: the terrorist and how the "war on terrorism", declared after the events of September 11 th, led by the United States, has suppressed freedoms and violated human rights, for new anti-terrorist legislation, military intervention and the imprisonment of "suspects". The US foreign policy is briefly discussed, contemplating its "imperialist logic". Finally, it is discussed how the Guantanamo prison represents a true state of exception, in which "suspects" of the practice of terrorist acts are kept for years without trial and deprived of all fundamental guarantees.